Ethics and the new materialism: a brief genealogy of the 'post' philosophies in the social sciences. Issue 1 (2nd January 2018) - Davies, Bronwyn
ABSTRACT: This paper explores the relation between poststructuralist theorising and new materialism with a particular focus on the work of Barad. Tracing the lines of thought, particularly as they relate to ethics, through the works of Foucault, Butler, Cixous and Deleuze the paper finds a range of concepts that anticipate and link directly with Barad's work. Barad's emphasis on the agency of matter, and on how matter is made to matter, is found to be new. The different analytic work that can be done with these various philosophers is explored through three intra-active entanglements; first, among preschool children and a rock, second, between a girl and a chimp raised as her twin, and third, between humans and cows.